Development of a mixing mechanism with a complex motion of the end-effector - Fomin, Alexey (Strojniški vestnik, 2019)
This study is focused on the development and analysis of a single-driven mixing mechanism, synthesized with a minimum number of links and joints. The end-effector of this mechanism is designed as a screw ending with a mixing element (blades) moving along a spatial trajectory. The end-effector is set between movable links in the kinematic chain of the mechanism. This allows increasing the working zone of the end-effector. The study provides kinematic analysis via an analytical method of coordinate transformations that have resulted in the detection of variable kinematic parameters (tilt angles and displacements in joints) depending on driving link rotation angle. Based on these results, the motion trajectory of the mixing element has been analytically determined and reproduced. Analytical findings have been verified by results of motion simulations. The presented mechanism is advisable to use for the preparation of various mixtures and levelling the concentrations and temperature of mixed substances. The mechanism can be used in the food, medical, chemical, and construction industries, as well as in agriculture.
Keywords: analitična kinematika; analytical kinematics; degree-of-freedom; kinematic pairs; kinematični pari; mešalni mehanizmi; mixing mechanism; prostorska trajektorija; prostostna stopnja; spatial trajectory